2022
DOI: 10.1038/s41598-022-08773-1
|View full text |Cite
|
Sign up to set email alerts
|

Weakly supervised end-to-end artificial intelligence in gastrointestinal endoscopy

Abstract: Artificial intelligence (AI) is widely used to analyze gastrointestinal (GI) endoscopy image data. AI has led to several clinically approved algorithms for polyp detection, but application of AI beyond this specific task is limited by the high cost of manual annotations. Here, we show that a weakly supervised AI can be trained on data from a clinical routine database to learn visual patterns of GI diseases without any manual labeling or annotation. We trained a deep neural network on a dataset of N = 29,506 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A study by Iizuka et al demonstrated high AUC values (0.96–0.99) for adenomas in the gastric and colonic epithelium by applying the same techniques, with few limitations [ 68 ]. A study on weakly supervised e2e AI in gastrointestinal endoscopy found that the AUC for the diagnoses of 13 diseases had a value of 0.7–0.8 and was able to predict the presence of colorectal cancer with an AUC > 0.76 [ 49 ]. The accuracy of a few CNN models in recognizing features in colorectal histopathological WSIs was compared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Iizuka et al demonstrated high AUC values (0.96–0.99) for adenomas in the gastric and colonic epithelium by applying the same techniques, with few limitations [ 68 ]. A study on weakly supervised e2e AI in gastrointestinal endoscopy found that the AUC for the diagnoses of 13 diseases had a value of 0.7–0.8 and was able to predict the presence of colorectal cancer with an AUC > 0.76 [ 49 ]. The accuracy of a few CNN models in recognizing features in colorectal histopathological WSIs was compared.…”
Section: Resultsmentioning
confidence: 99%
“…It accomplished good predictive performance in the identification of several diagnoses from gastrointestinal endoscopy images. This displays the potential of weakly supervised AI in clinical imaging modalities, in contrast to claims that manual annotations are a bottleneck for the future clinical application of AI [ 49 ]. The image dataset was preprocessed in MATLAB R2021a, and the ResNet-18 model was trained with the datasets.…”
Section: Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in this global vision, PGE became an instrument, in which synthesis of DNA/RNA fragments, vector assembly, and choice of the transformation method became directly available for the researcher, depending on the final research goal. So far, ML has already proven to be a revolutionary tool in supporting clinical studies, medical and precise diagnosis (Mansour et al, 2021;Fang et al, 2022) with application in medical diagnostics and for detecting, forecasting, and predicting of immunity responses (Nawaz et al, 2021;Buendgens et al, 2022). In this context, the utilization of an NGA for the comprehensive analysis of allergens could be completely revolutionary in human health.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in cases in which clinical data cannot be shared, federated learning, swarm learning and other techniques may help leverage the combined information from different datasets without actually merging them 15 . Third, the creation of public, large‐scale, not necessarily densely labelled, 16 datasets (‘GI ImageNet’ 17 ) would be a considerable step forward. These efforts, particularly the latter, may be cross funded by offering certification processes for commercial AI products against benchmarking datasets 13 .…”
mentioning
confidence: 99%